### How to solve word problems based on quadratic equations?

Solving word problems based on quadratic equations can be broken down into four simple steps:- Identity the unknown quantity and set it equal to a variable
- Identify the algebraic conditions
- Form a relevant quadratic equation from the above conditions
- Solve the equation to get the value of the unknown quantity

For example, consider the following instance of a word problem based on quadratic equations:

### An example

What is the area of a right triangle having a perimeter of 55 cm if the sum of its legs is 30 cm?

The solution to this word problem can be done in the three easy steps described above:

The solution to this word problem can be done in the three easy steps described above:

- Identity the unknown quantity and set it equal to a variable
- The unknown quantity is the area of the triangle. Let it equal to `A cm^2`
- Identify the algebraic conditions and form a relevant equation
- The algebraic conditions are that perimeter is equal to 55, and sum of the legs is 30 cm, and since it is a right triangle, the Pythagorean theorem as well. So if the three sides of the triangle are x, y and z, y being the hypotenuse, then we have the following equations corresponding to the given conditions:
- Perimeter is 55: `x + y + z = 55`
- Sum of legs is 30: `x + z = 30`
- Pythagorean theorem: `y^2 = x^2 + z^2`
- Form a relevant quadratic equation from the above conditions
- From the first two equations above we can clearly get the value of y by substituting the value of `x + z` in the first equation,
- `x + z + y = 55`
- `30 + y = 55`
- `y = 55 - 30`
- `y = 25`
- Substitute the value of `y` in the third equation,
- `y^2 = x^2 + z^2`
- `(25)^2 = x^2 + z^2`
- Solve the second equation either variable,
- `z = 30 - x`
- Substitute the above expression for x in equation 2(2) above,
- `(25)^2 = x^2 + (30 - x)^2`
- Solve the equation to get the value of the unknown quantity
- Change the equation to standard form
- `(25)^2 = x^2 + (30 - x)^2`
- `625 = x^2 + (30 - x)(30 - x)`
- `625 = 2x^2 - 60x + 900`
- `2x^2 - 60x + 275 = 0`
- Divide throughout by 2,
- `x^2 - 30x + 275 = 0`
- Solve by the quadratic formula,
- `x = (-b ± sqrt(b^2 - 4ac))/(2a)`
- `x = (30 ± sqrt((-30)^2 - 4*1*275))/(2*1)`
- `x = (30 ± sqrt(200))/2`
- `x = (30 ± 14.14)/2`
- `x = {(30 + 14.14)/2, (30 - 14.14)/2}`
- `x = {22.07, 7.93}`

Out of the above two solutions for `x`, the only positive one is taken to be the solution to for the word problem, since the variable `x` represents the length of the leg of a right triangle which can't be negative. So the length of one side is x = 22.07 cm. We already know the length of the hypotenuse y = 70 cm (see step 1 above) and from step 3, we know `z = 30 - x`, so `z = 30 - 22.07 = 7.93`

Therefore the dimensions of the triangle are 25, 22.07, 7.93.

Therefore the dimensions of the triangle are 25, 22.07, 7.93.

## No comments:

## Post a Comment